PHARMACOKINETICS AND PHARMACODYNAMICS OF ANTIMICROBIAL AGENTS IN PATIENTS WITH IMPAIRED RENAL FUNCTION: AMINOGLYCOSIDES - M. Kolesnyk; K. Zakon; V. Dudarenko (Ukrainian Journal of Nephrology and Dialysis, 2017)
This is review of aminoglycoside antibiotics pharmacokinetics and pharmacodynamics in patients with normal and impaired renal function. Dosing of different aminoglycosides in patients with different stage of renal function impairment and different modalities of renal replacement therapy are highlighted.